Search Title correct misconception in light of the book and Sunnah (Islamic Sciences Journal, 2023)
For serious understanding suqaim to Murad Alah's canon and for It is great harm on people , so the correction of conceptions has not been limited to our canon, instead  we found it in other previous canons .- Correct misconceptions according to the light of the holy Quran and these conceptions are :) holy men , guidness , gods , pessimism , death(- correct misconceptions according to the  light of prophets sunnah ,  and these concepts are :(  the pond , the will , Doubt about the power of Alah on the resurrection , workship of pontiffs and monks).
Keywords: alawlya', aitikhadh alalhat, almwt, almshyyt, al'ahbar.